The Making of Leaders Through Involvement in Curricular Activities: A Systematic Literature Review - Zuraina, Ali (Penerbit UMP, 2022)
The Behaviourist theroy explains that leaders are made and not born. Furthermore, the theory describes that an individual can become a leader when he or she is taught how to become one. The theory also suggests that learning through observation enables one to develop themselves as leaders. Therefore, the current systematic literature reviews investigate ways that university students can become leaders by participating in curricular activities. The study used PRISMA as the method to review the literature that was found on the described topic. Ten articles were employed to review the contents that were related to the area of the study. The systematic literature review found three (3) themes and six (6) sub-themes in which students can become leaders by involving themselves in the curricular activities. The study is significant for students who want or have the potential to become leaders in the future